FORMATION OF SIGNS OF THE PRESENCE AND TYPOLOGY OF CRISIS SITUATIONS IN THE ACTIVITIES OF AN ENTERPRISE - HRABOVSKA, Іryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the formation of signs of the presence and typology of crisis situations for the development of an effective anti-crisis mechanism for counteracting the impact of crises on the activities of industrial enterprises. The relevance is due to the high probability of crises, the need for anti-crisis management to collect information, develop scenarios for the development of crises, and preventive anti-crisis measures. The essence of the crisis as a managed process with signs of contradictions, cyclicality, and disruption of the viability of the system is determined. The essential signs of a crisis at the enterprise level are specified. The difference between a crisis, a crisis state, and crisis phenomena is highlighted. The author identifies categories of anti-crisis management problems for overcoming "crisis points" in the business cycle of an enterprise and preventing its bankruptcy: problems of monitoring the enterprise's business system, recognizing and diagnosing pre-crisis situations; problems caused by the state of key areas of the business system's functioning; problems related to the differentiation of types of managerial activities of the enterprise's management. The article substantiates the need to systematize the characteristics of the management object for grouping crises and reducing the dimensionality of crisis indicators when developing management decisions. Typical discriminatory signs (indicators) that distinguish crisis situations are proposed. A classification of crisis types is given according to their manifestation in the management object (subject localization). The typology of crises is considered, which includes a time (pre-, crisis, post-crisis phases) and a content (sudden, smoldering) perspective. Smoldering crises caused by management and their main stages are distinguished: strategic, structural, liquidity, cash flow, insolvency and insolvency. The generalization of scientific approaches to crisis management, provided that signals are detected in a timely manner and human and organizational factors are taken into account when developing effective anti-crisis solutions, allowed the author to present an improved approach to early monitoring for crisis prevention, which contributes to adaptation to new business conditions and increased resilience using modern anti-crisis management tools.
Keywords: crisis management; crisis situations; typology of crises; crisis state; management decisions; crisis prevention; smoldering crises; crisis strategies